Factor That Influence Online Consumer Buying Behavior with Reference to Nepalgunj city - Pokhrel, Lalmani (Academia Research Journal, 2023)
Phenomenon of online purchasing is increasingly gaining popularity among consumers. This is largely attributed to the benefits associated with it, such as time-saving, convenience, 24-hour availability, a wide variety of products, and the ability to compare brands and products. However, despite these benefits, consumers also perceive certain risks associated with online purchasing, including financial loss, product performance risk, delivery risk, trust and security, and website design. These perceived risks and psychological factors significantly influence consumers’ behavior towards online purchasing. Therefore, this study seeks to identify the online factors that affect consumers’ behavior towards online purchasing in the context of Nepalgunj. Specifically, the study aims to identify the perceived risk and psychological factors and understand the demographics of online consumers. The study reviewed recent literature on the topic and collected primary data through a well-structured questionnaire distributed online. Around 65 respondents were chosen from 30 students, 15 females from engaging in public service and 20 males were chosen from different occupation, as the distribution chain started from friend’s circle. The findings of the study suggest that perceived risk factors, such as financial risk, significantly affect consumers’ buying behavior towards online purchasing. Delivery risk and trust and security have an average impact on consumers’ buying behavior. Therefore, online retailers and marketers should address these risk factors and psychological concerns to encourage more online purchasing.